Pemanfaatan Museum Sejarah Al-Qur'an Sumatera Utara sebagai Sumber Sejarah - Rahmaputri, Chindy; Ritonga, Sakti; Yasmin, Nabila (Darul Yasin Al Sys, 2023)
This study aims to describe: 1) the history of the establishment of the Al-qur'an History Museum and its development to date, 2) what collections are in the Al-qur'an History Museum, 3) the use of the Al-qur'an History Museum as a historical sources. The main purpose of this research is to find out exactly how useful the collection of manuscripts which are the treasures of Islam is as a material for historical research and learning. This study uses a qualitative method with a descriptive approach. Informants in this study were the head of the museum, academic researchers, students. Data was collected through observation, interviews, and documentation. The results showed: (1) The history of the establishment of the Al-qur'an History Museum was motivated by anxiety and a lack of concern for Islamic artifacts in North Sumatra. So departing from this statement and the basis of ignorance, historian Ichwan Azhari tries to prove the existence of these Islamic artifacts through a long journey in finding them by tracing every area in North Sumatra. (2) The use of the Mushaf collections in the History Museum of Al-Quran in North Sumatra as a historical source for researchers can be seen from the use of these historical sources as the primary (primary) source and has the main goal of improving previous research. The collections in the museum make a major contribution to research so that a fact of Islamic treasures can be revealed.